Prolongued co-circulation of two distinct dengue virus type 3 lineages in the hyperendemic area of Medellín, Colombia (2010)
ABSTRACT: During the past two decades, Dengue virus-3 (DENV-3) has re-emerged in the Western Hemisphere causing significant epidemics of dengue fever (DF) and dengue hemorrhagic fever (DHF). In an effort to understand the molecular evolution of DENV-3 and their relationships to other DENV-3 circulating in the western hemisphere, we conducted a phylogenetic study on DENV-3 isolates made between 2002 and 2007 in the metropolitan area of Medellín, Colombia. An unexpected co-circulation of two different variants of DENV-3 subtype III during at least 5 years in Medellín was found. In addition, a more complete analysis of DENV-3 viruses isolated in other South American regions revealed the existence of three different subtype III lineages, all derived from independent introductions. This study documents significant genetic diversity of circulating viruses within the same subtype and an unusual capacity of the population of this city to support continuous circulation of multiple variants of dengue virus.